Targeting the Barriers in the Substance Use Disorder Continuum of Care With Peer Recovery Support. (December 2020) - Stanojlović, Milena; Davidson, Larry
Substance Use Disorder (SUD) has been recognized as a chronic, relapsing disorder. However, much of existing SUD care remains based in an acute care model that focuses on clinical stabilization and discharge, failing to address the longer-term needs of people in recovery from addiction. The high rates of client's disengagement and attrition across the continuum of care highlight the need to identify and overcome the obstacles that people face at each stage of the treatment and recovery process. Peer recovery support services (PRSS) show promise in helping people initiate, pursue, and sustain long-term recovery from substance-related problems. Based on a comprehensive review of the literature, the goal of this article is to explore the possible roles of peers along the SUD care continuum and their potential to improve engagement in care by targeting specific barriers that prevent people from successfully transitioning from one stage to the next leading eventually to full recovery. A multidimensional framework of SUD care continuum was developed based on the adapted model of opioid use disorder cascade of care and recovery stages, within which the barriers known to be associated with each stage of the continuum were matched with the existing evidence of effectiveness of specific PRSSs. With this conceptual paper, we are hoping to show how PRSSs can become a complementary and integrated part of the system of care, which is an essential step toward improving the continuity of care and health outcomes.